The Effectiveness of Learning English Vocabulary through Quizizz Games Application - Na'imah (English Education:Journal of English Teaching and Research, 2022)
The inspiration and innovation used to learn English are still minimal. The learning thatoccurs is to imitate, record, and maintain vocabulary. This condition makes students think learning English is troublesome. At the same time, English is considered necessary because it is an international language and is widely used. This article discusses how powerful English learning is in a fun and liked way for children, mainly through quiz games. The methodology used in this study is subjective. The researcher analyzes and collects information along with data on research topics and makes a difference to English coaches about their meetings when involving the Quizizz application as a learning medium to build student inspiration in learning English. The Quizizz game application teaching media makes students more interested in learning a language and makes teaching easy and effective. Based on the exploration directed by scientists, it is possible to reason that learning English through game applications is very powerful and ready to expand students' learning inspiration. Games are learning media that can create an exciting learning climate but do not reduce or reduce students' understanding of the material and can expand their learning inspiration in vocabulary learning. This educational game provides benefits in learning media because this media is exciting and can inspire considerable brain work and then use time productively. Keywords: English vocabulary, games quizizz, learning motivation